A single stranded fluorescent peptide probe for targeting collagen in connective tissues. Issue 87 (18th October 2017) - Cai, Xiangdong; Liu, Zhao; Zhao, Sha; Song, Chen; Dong, Shouliang; Xiao, Jianxi
Abstract : A novel single stranded fluorescent collagen mimetic peptide has been constructed by introducing a bulky FAM dye in the central region rather than the N terminus. Without the need for any prior thermal or ultraviolet treatment, the peptide probe can be conveniently applied to specifically target collagen in connective tissues for fluorescence imaging. Abstract : We herein report the construction of a novel single stranded fluorescent collagen mimetic peptide by introducing a bulky FAM dye in the central region rather than the N terminus. Without the need for any prior thermal or ultraviolet treatment, the peptide probe can be conveniently applied to specifically target collagen in connective tissues for fluorescence imaging.